Evaluating the pragmatic language skills of children with ADHD and typically developing playmates following a pilot parent-delivered play-based intervention - Cordier, Reinie; Munro, N.; Wilkes-Gillan, S.; Ling, L.; Docking, K.; Pearce, W. (Wiley-Blackwell Publishing Asia, 2016)
Background/aim: Children with attention deficit hyperactivity disorder (ADHD) often present with pragmatic language deficits and difficulties with peer-peer friendships. Parents and typically developing peers (TDPs) may be able to assist via parent and peer-mediated intervention approaches when adequately supported by trained adult facilitators. This study investigated whether a parent-delivered play-based intervention supported by occupational therapists and speech language pathologists was feasible and improved the pragmatic language skills of children with ADHD and their TDPs. Methods: Nine children with ADHD paired with nine TDPs (mean age = 8.2 years) participated. The seven-week intervention was delivered by parents of children with ADHD at their home and consisted of weekly assigned home-based modules, supported play-dates between the pairs of children and supplemented by three clinic visits. Parent adherence to intervention activity was monitored on a weekly basis. Blinded ratings of observed peer-peer play interactions were used to detect changes in pragmatic language from pre-post intervention and one month follow-up using the Pragmatic Observation Measure (POM). Results: All parents reported completing the seven weekly home-based modules and attended all clinic visits. Significant improvements in observed pragmatic language skills were found from pre-follow-up for both the ADHD and TDP children and pre-post for the ADHD children. Conclusion: The preliminary findings suggest that using parents to facilitate their child's pragmatic language skills was a feasible intervention approach with parents acting as agents of change to improve the pragmatic language of their children. This exploratory study identifies the need for further large-scale research to address the pragmatic language skills of children with ADHD using parent-delivery in a play-based, peer-peer context.